Intraoral administration of probiotics and postbiotics: An overview of microorganisms and formulation strategies - Mihajlo Bogdanović; Dragana Mladenović; Ljiljana Mojović; Jelena Djuriš; Aleksandra Djukić-Vuković (Universidade de São Paulo, 2024)
Abstract The last decade provided significant advances in the understanding of microbiota and its role in human health. Probiotics are live microorganisms with proven benefits for the host and were mostly studied in the context of gut health, but they can also confer significant benefits for oral health, mainly in the treatment of gingivitis. Postbiotics are cell-free extracts and metabolites of microorganisms which can provide additional preventive and therapeutic value for human health. This opens opportunities for new preventive or therapeutic formulations for oral administration. The microorganisms that colonize the oral cavity, their role in oral health and disease, as well as the probiotics and postbiotics which could have beneficial effects in this complex environment were discussed. The aim of this study was to review, analyse and discuss novel probiotic and postbiotic formulations intended for oral administration that could be of great preventive and therapeutic importance. A special attention has been put on the formulation of the pharmaceutical dosage forms that are expected to provide new benefits for the patients and technological advantages relevant for industry. An adequate dosage form could significantly enhance the efficiency of these products.